Innovative Redesign of an Umbrella Using Quality Function Deployment (QFD) and Theory of Inventive Problem Solving (TRIZ) - BIN YAHAYA, MUHAMMAD ZAKWAN; MOHAMMAD, MUSLI (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Umbrellas are essential tools for weather protection, yet many existing designs lack portability, ease of use, and adequate coverage; particularly for university students who require compact, reliable, and user-friendly solutions for daily mobility. One of the most critical issues identified is the need for umbrellas that are lightweight and foldable for easy carrying and storage, especially in backpacks or bags. The objectives of this project are to identify customer requirements for umbrellas, evaluate the importance of these requirements and the performance of existing umbrella designs, and propose design improvement using the Quality Function Deployment (QFD) and Theory of Inventive Problem Solving (TRIZ) methods. Data were collected through pilot interviews and a questionnaire survey involving 100 university students to capture users’ requirements. Based on the survey analysis, the top three prioritized customer requirements were: (1) lightweight and foldable for easy carrying and storage, (2) smooth operation, and (3) sufficient coverage to keep users and their belongings dry. The integration of QFD and TRIZ effectively translated the user requirements into technical specifications and guided innovation in the design process. As a result, a new umbrella concept was proposed, featuring a head-mounted design for hands-free operation and full coverage, along with lightweight materials and an enhanced opening mechanism. The final design was developed using SolidWorks software. This study demonstrates that combining QFD and TRIZ offers a structured and effective approach to user-centered product innovation.